ARTI PENTING WORLD VIEW PENDIDIK DALAM PENDIDIKAN - Hery Noer Aly (Ta'dib: Jurnal Pendidikan Islam, 2010)
This article will explain how can world view of educator influence on education, either its process or personality of its alumni. The explanation will analyze the urgency of world view in various activities of life, especially in education. It will also analyze world view as foundation and content of education, and then the relation between educator personality and education he holds. The writing in turn will show that world view can be made as a method of analysis to see a coherency and synchronization among the components of system.